What is the prevalence of chronic kidney disease among hypertensive non-diabetic Egyptian patients attending primary healthcare? - Silvana Nader Nagib; Saeed Abdelwahab; Ghada Essam El-Din Amin; Mohamed Farouk Allam (Clinical and Experimental Hypertension, 2023)
Background Although chronic kidney disease (CKD) is considered the major cause of morbidity and mortality in hypertension, the recognition and prevention of CKD remain deficient. CKD is one of the major health challenges in Egypt. CKD affects approximately 13% of the adult population, resulting in significant morbidity, mortality, and health care costs. Patients with more progressive stage 3 or stage 4 CKD experience a high rate of cardiovascular events and death compared to earlier stages of CKD. Aim This study was performed to determine the prevalence and risk factors of CKD among hypertensive non-diabetic patients attending primary health care (PHC) centers in Cairo. Methodology The study type is a cross-sectional study. Study setting: Two PHC centers: Saraya El-kobba and El-Sharabya. Sampling method: Recruitment of participants was done in one day weekly. Any known essential hypertensive patients aged 18 or more registered in the two PHC centers in Cairo. Results The prevalence of CKD was 33% among the hypertensive non-diabetic patients. Among CKD participants, the prevalence is more common in females (59.7%) than males (40.3%), in those who completed primary education and in the illiterates and low socioeconomic class. Surprisingly, it is more common in patients with positive family history of CKD and patients with ischemic heart disease and the antihypertensive drugs use. Conclusion CKD has a high prevalence among hypertensive non-diabetic patients, and it has a significant morbidity and mortality among those patients.